Energy-saving synthesis and β-phase enhancement of Cu2Se thermoelectric materials via the microwave hybrid heating technique - Rudradawong, Chalermpol; Sukwisute, Pisan; Limsuwan, Pichet; Harnwunggmoung, Adul; Horprathum, Mati; Sakdanuphab, Rachsak; Sakulkalavek, Aparporn (My University, 2021)
Thermoelectric generators harvest energy from waste heat and convert it to electricity. β-Cu2Se is a candidate for them due to its outstanding thermoelectric properties and its environmentally friendly component elements. A microwave hybrid heating (MHH) method was used for the fast synthesis and enhancement of β-Cu2Se materials. The effects of the MHH reaction time on the phase microstructure and thermoelectric properties of the Cu2Se material were investigated, and the MHH method was compared with the conventional heating method. The X-ray diffraction patterns of samples, synthesized via the MHH method, showed monoclinic- (α) and cubic- (β) Cu2Se crystalline structures, whereas a single monoclinic-(α) structure was identified in a sample, synthesized via a conventional heating method. In addition, the β-Cu2Se phase was enhanced with increased MHH reaction time. The carrier concentration increased with β-Cu2Se content, which increased electrical conductivity and decreased the Seebeck coefficient. The Cu+ ions in the β-Cu2Se phase led to the reduced thermal conductivity. A low thermal conductivity of 0.86 W m−1 K−1 and a maximum dimensionless figure of merit of 0.32 at 523 K were realized for 10 min MHH sample. Finally, MHH showed very low energy consumption and saved time, which are essential for industrialization.
Keywords: Energy saving synthesis; Microwave hybrid heating; Thermoelectric; β-Cu2Se